Analysis of The Most Widely Used E-Wallet and E-Commerce Portals in Indonesia Based on The Pillars of Digital Economy - Auliana Farabbanie Al-Arsy; Affan Afian (Nusantara Science and Technology Proceedings, 2022)
The rise in the development of the marketplace or e-commerce and e-wallet platforms has led to a significant increase in the number of payment system users. The Covid-19 pandemic has also contributed to the growth of e-commerce and e-wallets. Considering the rapid development of numerous integrated cooperations between platforms, it is not uncommon for market leaders to acquire other companies to add to their business realms. This research aims to analyze the largest and strongest e-commerce and e-wallet platforms in Indonesia about the pillars of the digital economy. The research method used was the qualitative descriptive method. Data was collected through a literature review, desk research, and questionnaires. Primary data was collected from the Travic website by using Similarweb. Research results showed that the e-commerce platforms with the highest criteria were Shopee, Tokopedia, Lazada, Blibli, and Bukalapak. The demographic criteria for this study were males and females with an age distribution range. From the analysis of e-wallets, it was found that the largest E-wallets in Indonesia were Ovo, LinkAja, Gopay, Shopeepay, and Dana. E-wallets are still often accessed through mobile web compared to using a desktop and the age range of e-wallet users was 18-44 years of age.